Juventude marcada: relações entre ato infracional e a Escola Pública em São Carlos - SP - Borba, Patrícia Leme de Oliveira (2012)
This research, from a socio-historical perspective, focused the theme of young urban popular authors of offense and their relationship with the Public School in the city of São Carlos, São Paulo. Its overall objective was to investigate the relationship between the condition of youth enrolled in poverty and their school careers steeped interventions by institutions recognized as protection, according to the Statute of Children and Adolescents, once sparked the offense, in our case, the Núcleo de Atendimento Integrado (NAI). To this end, we worked with the monitoring and reconstruction of life stories of young people who committed the offense as well as analyzed the school reporting of young graduates from NAI System since its introduction in 2000 until the year 2009. This resulted in the production of a database with information from 2969 school reportings and the reconstruction of 10 teenagers life stories. Using these two data sources based on the understanding that the statistics can offer visibility and ability to generalize what their life stories is restricted because of their uniqueness, while those same stories, the depth of description and the accumulation of information, can qualify and provide concreteness to statistical analysis. Thus, the main results that this work points that young people that living in poor urban neighborhoods, attending Public School and accumulating grade failing, grade/age distortion and a high turnover within and among schools are more likely to enter the social-justice system. We emphasize the need to review the award to adolescence brand of social vulnerability, focusing the care failure and vulnerable situations that arise in the medium term in relation to the offenses are placed since the Childhood. Thus, points that the Public School is a protective element in the life of these young people, showing to the education sector linked to other social policies and family/community care that still need to be undertaken in Elementary School. Finally, it identifies the inadequacy of the system of social educational measures, focusing on open environment, its inefficiency in relation to the insertion and monitoring of their adolescents in the regular education and the demonstration that the entry in this system entails the incompleteness and the 'failure' of school life. We hoped that this study can provide references for coping vulnerabilities surrounding the daily life of adolescents and young urban popular groups and the construction of a Public School with the ability, at the same time providing quality education for all and recognizing the unique demands of caring for their students. The logic here is that this school is possible, since articulated with the network of local protection, services and community, and the operators realize the complexity of life and necessities showed by their public.